ANALYSIS OF FARMER BEHAVIOR IN THE USE OF PERSONAL PROTECTIVE EQUIPMENT (PPE) ON PESTICIDE-USING FARMERS IN MELATI II VILLAGE, PERBAUNGAN DISTRICT, SERDANG BEDAGAI REGENCY - Putri Rahmadillah, Al Fiza; Rambe, Desi; Ibrahim, Dimas; Fakhri, Muhammad Puji; Pramita Gurning, Fitriani (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Background Rice farmers in processing their crops certainly use pesticides, as an eradicator of various kinds of pests that can attack rice. Pesticides have greatly helped farmers in preventing crop failure due to pests. However, improper use of pesticides can endanger the health of farmers. To prevent this, farmers must use complete PPE when spraying rice. The purpose: of this study is to see what factors are related to the use of PPE in farmers who use pesticides, in farmers in Melati II Village in 2023. Method: This type of research is quantitative with a cross-sectional approach, the sample of this study amounted to 100 farmers. Data collection using interviews, questionnaires, and observation techniques. The data obtained is then processed with chi-square statistical tests. Results: Based on the results of bivariate statistical tests knowledge variables and action variables are related to the use of personal protective equipment (PPE). The results of the study showed that the variables related to the use of PPE were knowledge variables (p = 0.004) and action variables (p = 0.043). Suggestion: It is expected for the local government to provide knowledge to farmers in Melati II Village, regarding the importance of using personal protective equipment when spraying pesticides and the dangers of pesticides, to protect nature and also the health of farmers.